Análise das expressões imunohistoquímicas da p53, bcl-2 e ki-67 no adenocarcinoma colorretal e suas correlações com os fatores prognósticos - Menezes, Hunaldo Lima de [UNIFESP] (2009)
Purpose: To analyse the immunohistochemical expressions of the proteins p53, bcl-2 e Ki-67 in colorectal adenocarcinoma and correlate it with the clinical pathological prognostic factors. Methods: A TMA paraffin block was constructed with colorectal carcinoma tissue of 82 patients who had undergone surgery in the Hospital Sao Paulo-UNIFESP, from 2002 to 2005, submitted neither to chemo or radiotherapy. Four ìm sections from the was submitted to immunohistochemistry and immunoexpression staining scores were obtained, than was correlated with the degree of cellular differential, stage, relapse-free survival, relapse, survival and specific mortality. The variables of the study were analyzed by tests of the qui-square and Kaplan-Meyer to verify the markers association. The significance of the differences between the curves of relapse-free survival and of the overall survival was analyzed by tests of lgrank and Wilcoxon. Results: The immunohistochemical expression of the p53 was found to be positive in 70 tumours (85,4%) and negative in 12 (14,6%). The bcl-2 was found to be positive in 26 (31,7%) and negative in 56 (68,3%). The immunohistochemical expression of the ki-67 was found to be positive in 62 (75,6%) and negative in 20 (24,4 %). There was no correlation statistically significant between the markers expressions separately and in conjunction, involving the degree of cellular differentiation, stage, relapse-free survival, survival and specific mortality. With respect the relapse, there was a correlation statistically significant with the positive expression of the ki-67 (p53=0,035). Conclusion: The immunohistochemical expression of the Ki-67 in colorectal cancer is related to the incidence of the relapse of the disease.